OP57 Socioeconomic patterning of food and drink advertising at public transport stops in the city of edinburgh, uk. (2nd September 2017) - Robertson, T; Lambe, K; Thornton, L; Jepson, R
Abstract : Background: Outdoor advertising has been shown to disproportionately promote unhealthy foods, with links to food preferences, purchasing and consumption habits. Given the socioeconomic inequalities in food quality, consumption and obesity, it is also possible that advertisers are disproportionally advertising unhealthy food products in lower socioeconomic areas. The aim of this study was to explore the socioeconomic patterning of food advertising at bus stops in Edinburgh, UK. Our hypothesis was that there would be a higher prevalence of unhealthy (fast food, soft drinks, confectionary etc.) versus healthy (water, low sugar beverages etc.) food advertisements situated in more deprived areas within the city. Methods: This study took place in Edinburgh, Scotland in 2015. In the city, there were 2227 bus stops, 447 of which had advertising shelters (20%). 'ODK collect', an open-source application, was used to record data at each bus stop including GPS coordinates, type of area (residential, industrial etc.), details about the food or drink product being advertised and whether a price or special offer was featured. GPS coordinates were converted to postcodes and then the area level measure of socioeconomic deprivation (Scottish Index of Multiple Deprivation; SIMD). SIMD scores were further converted into quintiles for analysis. Generalised Linear Models were used to compare the patterning of food adverts by area-level deprivation, with and without adjustment for ward size, population and area type. All analyses were conducted using SPSS version 21. Results: In total, 562 food advertisements were recorded across 298 bus stops, with a mean of 1.89 food advertisements per shelter. Over 85% of all advertisements were for food products. Nine categories of food and related advertisements were identified including alcohol, confectionary, coffee, fast food outlets, food stores, fruit juices, frozen desserts, iced coffee and soft drinks. No adverts for fresh fruit or vegetables (besides juices), water or low sugar beverages were recorded. Across all nine food categories there were no associations between increased prevalence of these adverts and deprivation level. For example, fast food outlet advertisements (which made up 39% of all food adverts) were no more likely to be present in lower versus higher socioeconomic areas (B=0.248, 95% CI: −0.082, 0.578, p=0.140). Discussion: While food advertisements were abundant across the city, there were no patterns related to the socioeconomic status of the areas where these were located. However, all could be classed as advertising unhealthy food and drink products. This study was limited by not considering other forms of outdoor advertising.